Evaluation of the cobas SARS-CoV-2 & Influenza A/B v2 assay for detecting SARS-CoV-2 and influenza A and B viruses in nasopharyngeal swab specimens - Eunjung Jeong; Minhee Kang; Hyeonseek Park; Ji-Youn Kim; Sun Ae Yun; Yun Young Cho; Jae-Hoon Ko; Tae Yeul Kim; Hee Jae Huh; Nam Yong Lee (Microbiology Spectrum)
ABSTRACT Accurate and rapid diagnostic assays that simultaneously detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza A/B are crucial for effective clinical management and infection control. In the present study, we evaluated the cobas SARS-CoV-2 & Influenza A/B v2 assay (Roche Diagnostics, Basel, Switzerland) using the Roche cobas 5800 system, comparing it to the Allplex SARS-CoV-2/FluA/FluB/RSV assay (Seegene, Seoul, Republic of Korea). A total of 871 nasopharyngeal swab specimens, including 164 SARS-CoV-2-positive, 76 influenza A-positive, 77 influenza B-positive, and 554 negative specimens, were tested using the cobas and Allplex assays in parallel. The positive percent agreement and negative percent agreement between the cobas and Allplex assays were 100% and 98.3% for SARS-CoV-2, 100% and 99.1% for influenza A, and 100% and 99.3% for influenza B, respectively. Cohen’s kappa values ranged from 0.95 to 0.96, indicating almost perfect agreement. The limits of detection for SARS-CoV-2 E and open reading frame 1ab genes, influenza A, and influenza B were 25.3, 12.4, 16.1, and 11.0 copies/mL, respectively. No cross-reactivity was observed with 29 non-target respiratory pathogens. These findings demonstrate that the cobas assay reliably detects SARS-CoV-2 and influenza A/B with high sensitivity and specificity. Notably, this assay enables high-throughput automated workflows, facilitating timely decision-making during SARS-CoV-2 and influenza cocirculation.IMPORTANCEAccurate and rapid diagnostic assays that simultaneously detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza A/B are essential for effective clinical management and infection control. This study demonstrates that the cobas SARS-CoV-2 & Influenza A/B v2 assay reliably detects SARS-CoV-2 and influenza A/B with high sensitivity and specificity. Designed for use on the cobas 5800/6800/8800 systems, this assay supports high-throughput automated workflows, enabling timely decision-making during periods of high testing demand, such as the cocirculation of SARS-CoV-2 and influenza.